The recombinant BMP-2 loaded silk fibroin microspheres improved the bone phenotype of mild osteogenesis imperfecta mice - Ting Fu; Yi Liu; Zihan Wang; Yaqing Jing; Yuxia Zhao; Chenyi Shao; Zhe Lv; Guang Li (PeerJ, 2023)
Osteogenesis imperfecta (OI) is an inherited congenital disorder, characterized primarily by decreased bone mass and increased bone fragility. Bone morphogenetic protein-2 (BMP-2) is a potent cytokine capable of stimulating bone formation, however, its rapid degradation and unanticipated in vivo effects restrict its application. The sustained release characteristic of silk fibroin (SF) microspheres may potentially address the aforementioned challenges, nevertheless they have not previously been tested in OI treatment. In the current investigation, recombinant BMP-2 (rBMP-2) loaded SF (rBMP-2/SF) microspheres-based release carriers were prepared by physical adsorption. The SF microparticles were characterized by scanning electron microscopy (SEM) and were investigated for their cytotoxicity behavior as well as the release profile of rBMP-2. The rBMP-2/SF microspheres were administered via femoral intramedullary injection to two genotypes of OI-modeled mice daily for two weeks. The femoral microstructure and histological performance of OI mice were evaluated 2 weeks later. The findings suggested that rBMP-2/SF spheres with a rough surface and excellent cytocompatibility demonstrated an initial rapid release within the first three days (22.15 ± 2.88% of the loaded factor), followed by a transition to a slower and more consistent release rate, that persisted until the 15th day in an in vitro setting. The factor released from rBMP-2/SF particles exhibited favorable osteoinductive activity. Infusion of rBMP-2/SF microspheres, as opposed to blank SF spheres or rBMP-2 monotherapy, resulted in a noteworthy enhancement of femoral microstructure and promoted bone formation in OI-modeled mice. This research may offer a new therapeutic approach and insight into the management of OI. However, further investigation is required to determine the systematic safety and efficacy of rBMP-2/SF microspheres therapy for OI.